PEDAGOGICAL FACTORS OF THE DEVELOPMENT OF CREATIVE THINKING OF SCHOOL AGE CHILDREN THROUGH THE EDUCATIONAL CLUSTER - Ziyadulloeva Farangiz Juraboy kyzy (Galaxy International Interdisciplinary Research Journal, 2022)
The article is devoted to the generalization of the features of the development of creative thinking in primary school and adolescence.